Hypermedia and Career Counselling for Personal Flexibility - do Céo Taveira, Maria (Canadian Journal of Counselling and Psychotherapy, 2011)
Computer-assisted career guidance systems (CAGS) are the most important technological innovation in career counselling in the last 20 years. Some information and learning CAGS have been recendy designed to assist clients in career-planning proficiency and personal autonomy and flexibility. In this sense, specialized research is needed to explore the innovative questions of Psychology/New Information Technology interface domain for career counselling and development. A computer-assisted career guidance system — PROJF.CTOS — for secondary students, and developed in Hypermedia, is presented. The goals, rationale, scope, structure, content and procedures of the system are exemplified. Advantages of designing Hypermedia for career counselling for personal flexibility are discussed.